DEVELOPING WRITTEN ENGLISHWEB-BASED MATERIALS FOR JUNIOR HIGH SCHOOL STUDENTS (English Education Journal, 2013)
The research tried to answer some problems: (1) the lack of online written materials for seventh grade students outside the school or during day-off; (2) what kinds of online materials the seventh graders needed; (3) how was online materials developed; (4) how effective was the online materials, and (5) what were the advantages and disadvantages of the online materials. The researcher adopted some steps in educational research and development proposed by Borg and Gall in Junior High School 21 Semarang. The researcher chose one class of sevent graders that had 24 students in it. In conducting the study, the researcher observed the existing materials and interviewed the teacher for the need analysis. After that, the researcher developed the online materials, then conducted the expert validation to some experts and tests and gave questionnaires to the students. The researcher, then, calculated the productâ€™s effectiveness by using t-test. It was found out that the product wasÂ  considered effective based on the t-test result and very good based on the questionnaire analysis. There were also some online materials available, yet they were not so attractive and complete. Finally, the researcher also found out some advantages and disadvantages from the product.